Penerapan Metode SWARA dan Grey Relational Analysis Dalam Pemilihan Karyawan Terbaik - Very Hendra Saputra; Setiawansyah Setiawansyah (PT. Tech Cart Press, 2024)
The best employees are individuals who not only have exceptional expertise in their work, but also stand out in their attitude, dedication, and engagement towards the job and the company. One of the problems that often arises in the selection of the best employees is the lack of congruence between the skills possessed and the lack of transparency and communication in the best employee appraisal process to understand what is expected by the company. This study aims to select the best employees by applying a combination of the SWARA method for determining the weight of criteria and the GRA method for selecting the best employees based on the data from the assessment results that have been carried out. The final score ranking results recommend for the best employee 1 with a final score of 0.1799 on behalf of Desi Puspasari, the best employee 2 with a final value of 0.1147 on behalf of M. Budianto, and the best employee 3 with a final score of 0.1082 on behalf of Akhmadi.